Exploring The Use Of Word Wall Gamification In Vocabulary Learning: Students’ Perceptions And Engagement - Fikri, Muhammad Izza Miftahul; Aisyah, Siti; Musyrofah, Lailatul; Prasetyo, Yudy; Andayani, Endah Alamsari (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the integration of a gamified Word Wall in vocabulary instruction and examines students’ perceptions and engagement with this Word Wall. Conducted with ten students from the English Education Study Program at Universitas PGRI Delta Sidoarjo, the research employed a descriptive qualitative design. Data were gathered through observations, interviews, and field notes. The findings suggest that incorporating gamification elements such as points, challenges, and collaborative tasks enhanced students’ motivation, vocabulary retention, and active participation. Students engaged actively in group and individual activities, communicated effectively, and responded positively to learning challenges. Despite these benefits, the study identified challenges including limited instructional time and varying levels of student motivation. Some participants found the activities demanding, especially when balancing academic workloads. Overall, the use of the gamified Word Wall contributed to a positive, interactive, and student-centered learning environment. The study highlights the importance of considering learners’ individual differences and educational contexts to ensure the sustainability of gamified strategies. These insights offer practical implications for enhancing vocabulary learning through engaging, participatory methods.